Relationship Between Income and Husband's Support In Participation With Via Screening Method In Sexual Productive Women - Kristina Haloho, Sri Dewi; Zuhriyah, Lilik; Ratnaningrum, Safrina Dewi (Devotion : Journal of Research and Community Service, 2022)
Cervical cancer is the second most common cancer in women worldwide after breast cancer. The high incidence of cervical cancer is due to delays in diagnosis and patients coming in with advanced cancer conditions; it is necessary to have cervical cancer screening so that it is not too late in treatment. One cervical cancer screening that can be done is the visual inspection with the acetic acid (VIA) method. Based on the existing phenomena, not all women of childbearing age want to do the VIA examination because they feel ashamed, lack knowledge regarding the importance of VIA, fear feeling sick during the examination, and lack of husband's support. This study aims to determine the relationship between income level and husband's help with participation in cervical cancer screening using the VIA method in women of childbearing age. This type of research is a quantitative study with a cross-sectional approach. The research sample is women of childbearing age, which meets the sample criteria by using simple random sampling of as many as 120 respondents. The instrument used is a questionnaire and data analysis using Chi-square. The results showed a relationship between the level of income and the husband's support with participation in cervical cancer screening using the VIA method at WUS in Tandun I District, with p-values of 0.010 and 0.028 (p-value <0.05). The conclusion is that an increase in income or the provision of material support and the husband's support can make his wife carry out an IVA examination. Therefore, it is hoped that what should give an increase in income or the provision of materials support and a husband's license to the wives of couples of childbearing age to prevent cervical cancer and reduce cervical cancer mortality